THEORETICAL RESEARCH ON OBSERVATIONAL METHOD WITH PARAMETRIC CURVE BY EFFICIENCY EVALUATION OF VIBRATORY STRESS RELIEF - GAO YongYi; LI ZhiGao; FU XiangYun; ZOU DaiFeng (Jixie qiangdu)
This paper based on nonlinear rectangular thin plates with butt welding residual stress as the research objects. According to the theory of nonlinear vibration, It has study the influence of the welding residual stress on the natural frequency and the maximum value of amplitude in nonlinear component and explain that the parameters of VSR in theoretically. In addition, It’s obtains that the relationship between maximum amplitude and the natural frequency with steady-state response of nonlinear rectangular plates is nonlinear variation according to the welding residual stress. The conclusion is that maximum amplitude is reducing as the welding residual stress increasing, the natural frequency is reducing with the welding residual stress reducing.